Hypermethylation of the SEPT9 Gene Suggests Significantly Poor Prognosis in Cancer Patients: A Systematic Review and Meta-Analysis - Shen, Na; Wang, Ting; Li, Delei; Zhu, Yaowu; Xie, Huaping; Lu, Yanjun (Frontiers in Genetics, 2019)
Background: Aberrant hypermethylation of the Septin 9 (SEPT9) is an early event in several human cancers, and increasing studies have reported good performance of methylated SEPT9 (mSEPT9) in cancer diagnosis. Recent studies further focused on its value in cancer prognostic, but results are not clearly elucidated. Methods: A comprehensive search to identify relevant studies about the association between mSEPT9 and cancer prognosis was conducted through the EMBASE, PubMed, and Web of Science databases (up to January 2019). The main outcomes were overall survival (OS) and disease-free survival (DFS). The hazard ratio (HR) and 95% confidence interval (95% CI) for OS and DFS was extracted from each included study and pooled by using a random-effects model. Results: Ten eligible studies comprising 1266 cancer patients were included. Results demonstrated that mSEPT9 was associated with poor OS (HR = 2.07, 95%CI = 1.40-3.06). Specially, mSEPT9 detected in preoperative plasma predicted worse OS in cancer patients (HR = 3.25, 95%CI = 1.93-5.48). In addition, we also identified a significant association of mSEPT9 with decreased DFS of cancer (HR = 3.24, 95%CI = 1.81-5.79). Conclusion: Our meta-analysis supports that mSEPT9 is associated with reduced OS and DFS in cancer patients. Moreover, detection of mSEPT9 using plasma appears to be a convenient and promising way to predict long-term survival of cancer patients.